2018
DOI: 10.1158/1055-9965.epi-17-1101
|View full text |Cite
|
Sign up to set email alerts
|

Transducin-Like Enhancer of Split 3 (TLE3) Expression Is Associated with Taxane Sensitivity in Nonserous Ovarian Carcinoma in a Three-Cohort Study

Abstract: Chemoresistance is a major challenge in ovarian cancer treatment, resulting in poor survival rates. Identifying markers of treatment response is imperative for improving outcome while minimizing unnecessary side effects. We have previously demonstrated that expression of transducin-like enhancer of split 3 (TLE3) is associated with favorable progression-free survival in taxane-treated ovarian cancer patients with nonserous histology. The purpose of this study was to perform an independent evaluation of the ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…TLE proteins have been observed to interact with transcriptional factors, including Hes, c-Myc, and Runx (12,13). Additionally, some studies have reported that TLE1 and TLE3 can participate in tumor development as tumor suppressor genes (14)(15)(16)(17).…”
Section: Introductionmentioning
confidence: 99%
“…TLE proteins have been observed to interact with transcriptional factors, including Hes, c-Myc, and Runx (12,13). Additionally, some studies have reported that TLE1 and TLE3 can participate in tumor development as tumor suppressor genes (14)(15)(16)(17).…”
Section: Introductionmentioning
confidence: 99%
“…In AML cell lines, loss of TLE4 and Wnt signaling pathway activation increased the expression of proinflammatory genes and induced resistance to chemotherapy (Shin et al, 2016). In studies of ovarian and breast cancers, increased TLE3 expression was related to a higher response rate to taxane-based chemotherapy, but TLE3 expression showed no predictive value in treating breast cancer at an early stage (Samimi et al, 2012;Ring et al, 2018). The level of TLE3 expression was also found to be positively correlated with the sensitivity of breast cancer cells to tamoxifen treatment (van Agthoven et al, 2009).…”
Section: Tles Are Involved In Resistance To Cancer Therapymentioning
confidence: 99%
“…Further evidence from recent studies showed that genetic deletion of TLE genes in mice could cause significant defects, especially in the hematopoietic, neuronal, and musculoskeletal systems (Gasperowicz et al, 2013;Wheat et al, 2014;Ramasamy et al, 2016). Moreover, TLEs are abnormally expressed in various tumors and are involved in tumorigenesis (Dayyani et al, 2008;Holmes et al, 2012;Okada et al, 2017;Ring et al, 2018;Palit et al, 2019;Wang et al, 2020). TLEs also regulate the development of progenitor immune cells, and their function in mature immune cells is increasingly being recognized (Wheat et al, 2014;Ramasamy et al, 2016;Xing et al, 2018;Zhang et al, 2019).…”
Section: Introductionmentioning
confidence: 99%